Transient flow simulation of diseased and normal aorta - Nurain Afrizal, 1996-, author 626102 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2019)
Project Paper (Sarjana Muda Kejuruteraan (Bio-Perubatan)) - Universiti Teknologi Malaysia, 2019